Régió és világpiac az élelmiszergazdaságban - Nagy, Frigyes (Közép-Európai Közlemények, 2010)
There are several types of maps of Europe. There are maps of administration, of geology, hydrogeology. Knowing the historical changes it is perhaps better to look at the geographical maps formed by nature. Hungarian counties were formed also on this basis, building on the natural units of the landscape. In the course of history administrative maps have been diverted from them. But the European Union is tending back to the original idea of „region”, based on natural geographical units. This is also true for Hungary. We can notice the formation and cooperation of larger and smaller regions even there, where natural units are separated by country borders. But we are still at the beginning. Utilizing the special characteristics of the regions is one of the competitive edge that should be carried on better on national and global markets as well.